Introduction To Fun Role Play Method For Early Children's Development - utami, winda sherly; zubaidah, zubaidah zubaidah; Handayani, Lusi; Harahap, Nur Hasanah (MARAWA: Jurnal Masyarakat Religius dan Berwawasan, 2023)
: The role play method is also known as role playing. Role playing is a learning method that is fun for children, and is a method that is able to optimize the growth and development of children or students according to the standard level of development achievement. The aim of this competition is to provide knowledge to PGPAUD Study Program students regarding fun role play methods for early childhood. This trial is carried out through several stages, namely the foundation laying or building foundation phase, the research design stage, data gathering and analysis stage, and the acting on findings stage on research results. The result of this service is that students can implement roles that are a fun learning method for young children. The conclusion that can be drawn is that innovation is needed in learning, one of which is implementing fun role playing for children, which can then be used as a reference for future researchers regarding other aspects that can be developed in learning for early childhood.